Minimally Invasive Surgery Using Abramson Method Is Safe and Successful in Pectus Carinatum Deformity - Kılıç, Burcu; Güler, Gökberk; Sarbay, İsmail; Khoraki, Yaman; Erşen, Ezel; Kara, Hasan Volkan; Demirkaya, Ahmet; Turna, Akif; Kaynak, Kamil (Cerrahpaşa Medical Journal, 2022)
Objective: Pectus carinatum is the second most common congenital deformity after pectus excavatum. While pectus carinatum deformity has been corrected with open surgery (Ravitch) for nearly 50 years, a minimally invasive correction procedure was defined by Abramson in 2005. Methods: The Abramson procedure, which has been adopted by many centers, was applied to 68 patients with pectus carinatum deformity between 2010 and 2021 in our clinic. All patients who underwent surgery during this period were evaluated for clinical features, postoperative complications, patient satisfaction, and long-term results. Results: All patients in this study were male. There was no female patient who applied to the polyclinic and did not undergo surgery. The mean age of the patients was 16.7 years and 28.5% of the patients had a family history of pectus deformity. The mean follow-up period of the patients whose bar was removed was calculated at 27 months. No complications were observed. No patient had recurrence after bar removal. Considering the mid-long term complications, intense pain required the use of painkillers for 3 months in 7 (10.2%) patients and a break in the wire suture was detected after the second year in 4 (5.8%) patients. Conclusion: Abramson technique should be preferred to open surgery in suitable patients. It can be used safely in cases where brace application is not sufficient or in deformities that do not have a brace indication. Cite this article as: Kılıç B, Güler G, Sarbay İ, et al. Minimally invasive surgery using abramson method is safe and successful in pectus carinatum deformity. Cerrahpaşa Med J. 2023;47(1):55-59.